Characterization of PACs profile and bioactivity of a novel nutraceutical combining cranberry extracts with different PAC-A oligomers, D-mannose and ascorbic acid: An in vivo/ex vivo evaluation of dual mechanism of action on intestinal barrier and urinary epithelium. (November 2021) - Faggian, Marta; Bernabè, Giulia; Valente, Marco; Francescato, Stefano; Baratto, Gianni; Brun, Paola; Castagliuolo, Ignazio; Dall'Acqua, Stefano; Peron, Gregorio
Graphical abstract: Highlights: A tailor-made cranberry extract (CB-B) was prepared and characterized by HPLC-FLD-MS. CB-B was mixed to D-mannose and ascorbic acid in a novel nutraceutical (URO-F). URO-F can prevent urinary-tract infections due to its dual mechanism of action. Urine collected after CB-B and URO-F intake shows antiadhesive properties ex vivo. URO-F restores damages of intestinal epithelium induced by E. coli infection in vitro. Abstract: In this paper, an A-type procyanidin (PAC)-rich cranberry extract (CB-B) was obtained mixing different extracts and was formulated with D-mannose and ascorbic acid to obtain a novel nutraceutical (URO-F) aimed at preventing non-complicated bacterial urinary tract infections (UTIs). To assess the bioactivity of CB-B and URO-F, urine samples collected from six healthy volunteers undergoing a 2-days oral consumption of 0.41 g/day of CB-B or 10 g/day of URO-F (corresponding to 72 mg/day of PACs) were tested against uropathogenic E. coli (UPEC) incubated on urinary bladder epithelial cells (T24). Urinary markers of CB-B and URO-F consumption were assessed in the same urine output by UPLC-QTOF-based untargeted metabolomics approach. CB-B and URO-F were evaluated for their ability to promote the intestinal barrier function by restoring the trans -epithelial electrical resistance (TEER) and to inhibit the production of inflammatory cytokines in intestinal epithelial Caco2 cells. CB-B was characterized by a high PAC-A content (70% of total PACs) and a broad distribution of different PACs polymers (dimers-hexamers). Urine from subjects consuming CB-B and URO-F showed a significant effect in reducing the adhesion of UPEC to urothelium in vitro, supporting their efficacy as anti-adhesive agents after oral intake. CB-B inhibited the release of cytokine IL-8, and both products were effective in restoring the TEER. Overall, our results show that the beneficial effects of CB-B and URO-F on UTIs are not only due to the antiadhesive activity of cranberry on UPEC in the urothelium, but also to a multi-target activity involving anti-inflammatory and permeability-enhancing effects on intestinal epithelium.